Middle-Low Grade Phosphate Beneficiation and Recycling of Flotation Wastewater in China (789f099d-824c-424a-82ef-5ee1f0959a1e) - Kang N. Zhong; Yi H. Wei; Hui H. Luo; Yu L. Wang (International Mineral Processing Congress, 2003)
"More than 85% of phosphorous reserves in China occur as middle-low grade phosphate of sedimentary origin. The main gangues are dolomite, quartz, silicates, and clays. The characteristics of minerals are finely disseminated. Flotation results have shown that the floatability of apatite of this kind of ore is much worse than that of igneous and metasedimentary origin because of its high specific surface area. Although some effective depressants, such as naphthalene sulfonate and phenanthrene sulfonate, are used to decrease the MgO content in the P2O5 concentrate, its presence is still high (about 2%) in the Chinese concentrates. Meanwhile, the wastewater may cause some environmental problems. Batch flotation results and measurements of specific surface area and CO3 2- have revealed that there is a relationship between the floatability of apatite and the surface area.A two-stage flotation flowsheet, which includes a combination of direct and reverse flotation, was developed for beneficiating sedimentary phosphate ores. The direct flotation was conducted in an alkaline medium and most of the apatite and carbonate minerals floated leaving quartz and siliceous gangue in the sink. In the reverse flotation circuit, the floated product was further beneficiated in an acidic medium to eliminate the carbonate as a float product. Apart from the high quality of concentrate, the two-stage flotation also facilitated the treatment and the recycling of wastewater. A wastewater recycling procedure was developed and tested in a continuous flotation process. The key factor was the careful selection of effective and non-toxic reagents."